Hakikat Inovasi (Discoveri, Invensi, Inovasi, Dan Modernisasi) - Piqriani, Yelmi Novita; Yurika, Muti’a; Amin, Alfauzan (GHAITSA : Islamic Education Journal, 2021)
This paper aims to find out information technology-based pie learning innovations. This research method uses literature research or library research to be analyzed and concluded. In collecting data, the writer uses this qualitative approach which wants to see innovations in Islamic Religious Education (PAI) learning. This research is qualitative by examining relevant sources using descriptive analysis methods. In it library research, by collecting, classifying, analyzing data from various sources that are relevant by way of observation or observation. Therefore, technological innovation can lead to needs and vice versa. Some change agents create need among their clients by demonstrating the existence of desirable new ideas. Knowledge of the existence of this innovation can create motivation for its adoption. Types of Knowledge about Innovation. Innovation consists of different types of knowledge. Innovations typically contain software information, which resides in the innovation and serves to reduce uncertainty about the cause-and-effect relationships involved in achieving the desired result.